Synthesis and computer-assisted design of mitochondrial electron transport-chain inhibitors as antimalarial agents - Carrasco, Marta Andreia Pais, 1983- (2014)
Tese de doutoramento, Farmácia (Química Farmacêutica e Terapêutica), Universidade de Lisboa, Faculdade de Farmácia, 2014